The experiences of ferric carboxymaltose desensitization and provocation - Fatma Dindar Çelik, MD; Kurtuluş Aksu, MD; Özgür Akkale, MD; Hatice Çelik Tuğlu, MD; Melis Yağdıran, MD; Onur Telli, MD; Gürgün Tuğçe Vural Solak, MD; Enes Çelik, MD (World Allergy Organization Journal)
Background: To present the characteristics of drug hypersensitivity reactions (DHR) among iron preparations and to describe the outcomes of rapid drug desensitization (RDD) and drug provocation tests (DPT) of ferric carboxymaltose (FCM). Methods: The retrospective descriptive study comprised patients with hypersensitivy to iron supplements. Low-risk according to the index reaction with iron, 10 patients underwent a 4-step DPT with FCM; an 11-step RDD protocol was administered to 21 patients not classified as low-risk. RDD success was evaluated for each cycle separately, defining successful completion as the implementation of all steps in both RDD and DPT protocols without subsequent early and/or late reactions. Results: Among the 21 patients (mean age: 41.73 ± 10.98 years, all female) hypersensitive to iron underwent FCM RDD, 20 patients (95.2%) successfully completed FCM treatment with RDD. RDD failed in only 1 patient (4.8%). The total number of desensitization cycles was 29, of which 28 (96.5%) were successful. Urticaria was the most common breakthrough hypersensitivity reaction and observed in 7 (33.3%) patients. Ten patients received FCM with DPT. The iron replacement therapy for these 10 patients was successfully completed. Urticaria developed in 2 patients after the completion of DPT. Conclusions: RDD is a dependable procedure facilitating the efficient delivery and completion of FCM treatments in patients with iron hypersensitivity. Additionally, FCM can be applied with DPT in low-risk patients.